A new green approach for the reduction of consumed solvents and simultaneous quality control analysis of several pharmaceuticals using a fast and economic RP-HPLC method; a case study for a mixture of piracetam, ketoprofen and omeprazole drugs. Issue 25 (1st June 2022) - Abdelgawad, Mohamed A.; Abdelaleem, Eglal A.; Gamal, Mohammed; Abourehab, Mohammed A. S.; Abdelhamid, Nessreen S.
Abstract : We report a novel and green RP-HPLC method able to separate and quantify a tertiary mixture of piracetam, ketoprofen and omeprazole produced by the same manufacturers. Abstract : One of the main aims of green analytical chemistry (GAC) is the reduction of solvents and chemicals consumed. Recycling the mobile phase in chromatographic techniques provides an efficient way to implement GAC principles. However, this is not an easy job, particularly in the case of the gradient mode. Analysis of multi-pharmaceuticals for the same manufacturer using one mobile phase system dramatically reduces consumed solvents, time, and cost for pharmaceuticals analysis in quality control laboratories. This work is an attempt to reduce time, cost and effort needed for quality control analysis of several dosage forms produced by the same manufacturer. Our novel and green RP-HPLC method is able to separate and quantify a tertiary mixture of piracetam, ketoprofen and omeprazole produced by the same manufacturers. The analyst can easily quantify the three drugs in the three dosage forms in one run using the gradient elution mode of methanol and water (from 50% methanol to 85% methanol in ten minutes) with a flow rate 1.5 mL min −1 on a non-polar C18 column. Suitable dilutions were done for the working solution of the mixed pharmaceutical formulations prior to chromatographic analysis. This procedure will dramatically reduce the consumed solvents and save time and money during pharmaceutical analysis. The calibration ranges are (5–25), (5–25) and (3–20) μg mL −1 for the three studied drugs. The International Council for Harmonization (ICH) procedures were followed in the validation process and the results were evaluated in comparison with official HPLC methods, where no noteworthy differences were found. The green profile of the method and pictograms of AGREE and Green Analytical Procedure Index (GAPI) approaches proved the eco-friendly character for the studied drugs. The simultaneous quantitative analysis for Stimulan® and Hyposec® capsules, and Ketolgin® tablets from the Amoun Pharmaceutical Company, Egypt, can be accomplished via the novel method. Also, Memoral® ampoules, Topfam® tablets, and Gastroloc® capsules from Sigma Pharmaceutical Industries, Egypt, could be analyzed simultaneously. Omez® capsules and Ketogesic® tablets from the Pharaonia Pharmaceuticals, Egypt, could be determined simultaneously too. Applying this RP-HPLC method, a significant reduction of the total cost is assured as the required amount of solvent is noticeably decreased when performing multi-analyses in comparison to single component analysis.